Analisis Perkembangan Olahraga Rekreasi Push Bike Ditinjau Pada Event “Pushbike Fun Race” Taman Ghanjaran Trawas Mojokerto - M Abdur Rohman Azis; Hijrin Fithroni; M Dzul Fikri; Andun Sudijandoko (Jurnal Kajian dan Penelitian Umum, 2024)
This study aims to determine the impact and role of the "Pushbike Fun Race" Event on the development of Push Bike sports in Mojokerto Regency as well as to find out the SWOT analysis owned in the implementation of the "Pushbike Fun Race" Event. The type of research used is qualitative research using interview, documentation and observation methods. The subjects in the study used 3 data sources, namely the chairman of KORMI Mojokerto Regency, the guardians of the participants, and the organizing committee. The results of the data analysis of this study show that there are various impacts after the event, including the Push Bike sport is now in the stage of entering the Community Sports Organization Branch, many people around the event location are interested in Pushbike sports, and it is one of the promotional events for tourist attractions. Meanwhile, the role of the "Pushbike Fun Race" event includes creating a positive image of the Push Bike event in Mojokerto Regency, as a liaison between Push Bike sports activists and institutions in Mojokerto Regency, and as a starting point for organizing the Push Bike event in Mojokerto Regency. Meanwhile, the results of the SWOT analysis show that the internal factor is balanced between strengths and weaknesses, in contrast to external factors, the opportunity factor is more dominating than the threat factor. It can be concluded that the "Pushbike Fun Race" event creates various impacts and positive roles for the development of Pushbike sports in Mojokerto Regency, then the SWOT analysis shows that the opportunity factor is more dominating than the other three factors contained in the "Pushbike Fun Race" event.